(untitled) (Research, Society and Development, 2022)
Purpose: Compare the evolution of indicators of nutritional status and eating habits between preterm newborns (PTNB) and term newborns (RNT). Methods: This is an observational, analytical, cohort study, with ambispective data collection. Data collection occurred of Mafra-SC through identification data, breastfeeding assessment, nutritional and anthropometric assessment, from the moment of hospital discharge until the six months of corrected age. Results: The sample consisted of 80 newborns, 40 of them were PTNB and the other 40 were RNT. When comparing anthropometric measurements, significant weight, height and head circumference gains were achieved in the two groups. The median Z-score for weight and height was adequate, indicating good weight gain and linear growth. As for the frequency of exclusive breastfeeding, at 6 months, only 20% of newborns and no PTNB (p <0.001) were exclusively breastfed and the frequency of difficulty in breastfeeding was low in both groups. Conclusion: Although the anthropometric assessments are similar, the recommended feeding practices, which include breastfeeding up to 6 months and the introduction of food after 6 months are below expectations, especially in PTNBs.